2014
DOI: 10.1002/acp.3049
|View full text |Cite
|
Sign up to set email alerts
|

Affect Regulation During Learning: The Enhancing Effect of Cognitive Reappraisal

Abstract: Affective experiences routinely occur during learning and need to be successfully regulated. In two experiments, we used an intervention that combined elements of utility value and cognitive reappraisal to gauge its effects on engagement and performance. We predicted that participants using the reappraisal strategy would experience more engagement and higher learning outcomes than controls. Ethnically diverse adult learners ranging from 18 to 58 years of age (Experiment 1, N = 93; Experiment 2: N = 138) used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 79 publications
2
27
0
Order By: Relevance
“…Current results are in line with Ben-Eliyahu and Linnenbrink-Garcia’s (2013) findings which demonstrated that reappraisal, when compared to suppression and rumination, supports SRL. Furthermore, reappraisal has been demonstrated to be useful as an intervention to improve comprehension in learning and related to higher learning achievements ( Strain and D’Mello, 2015 ). As SRL has been found to enhance achievements ( Miksza, 2015 ), the findings of the present study, together with earlier research, suggest that this relationship between reappraisal and achievement found by Strain and D’Mello (2015) can be explained by a higher use of SRL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current results are in line with Ben-Eliyahu and Linnenbrink-Garcia’s (2013) findings which demonstrated that reappraisal, when compared to suppression and rumination, supports SRL. Furthermore, reappraisal has been demonstrated to be useful as an intervention to improve comprehension in learning and related to higher learning achievements ( Strain and D’Mello, 2015 ). As SRL has been found to enhance achievements ( Miksza, 2015 ), the findings of the present study, together with earlier research, suggest that this relationship between reappraisal and achievement found by Strain and D’Mello (2015) can be explained by a higher use of SRL.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive reappraisal has been found to be one of the most effective ways of regulating negative emotions (Gross and Thompson, 2007). Strain and D'Mello (2015) conducted an intervention study and found that adult learners achieved better scores than a control group who received no intervention when using cognitive reappraisal. Reappraising learners not only experienced more positive emotions but, more importantly, experienced activating positive emotions (i.e., alertness and engagement) which correlate positively with learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, research has shown that the cognitive consequences of different emotion regulation strategies may be different. For example, Strain and D'Mello (2015) found that students who used cognitive reappraisal strategy reported more affective engagement and achieved better learning outcomes than those who did not use any strategy. Dillon et al (2007) reported that cognitive reappraisal strategy (cognitive up-regulation and cognitive down-regulation) rather than expressive suppression strategy promoted the memory of emotional materials.…”
Section: Learners' Emotions Regulation Strategiesmentioning
confidence: 99%
“…Because reappraisal comprises cognitions centered on the feedback, it is an engagement strategy and thus also serves improvement goals (Naragon-Gainey, McMahon, & Chacko, 2017). Indeed, participants instructed to use reappraisal during a learning task reported higher levels of positive affect and performed better, compared with participants who did not receive reappraisal instructions (Strain & D’Mello, 2015).…”
Section: The Model Of Motivated Feedback Disengagementmentioning
confidence: 99%